Prevalence and predictors of workaholism among managers - Ribeiro Souto Pinheiro, Letícia; Carlotto, Mary Sandra (Revista de Psicología, 2018)
This study aimed to identify the prevalence and predictors of workaholism in a sample of 392 Brazilian managers. We used a sociodemographic and occupational questionnaire, the Dutch Work Addiction Scale, the Utrecht Work Engagement Scale, the Satisfaction with Life Scale and the Regulatory Focus Scale. Data analysis was performed by multiple linear regression for the two dimensions of work addiction, excessive and compulsive working. The dimension of excessive working revealed a predictive model which consists of the following variables satisfaction with life, dedication, absorption, daily hours of technology use and type of bond, whereas the dimension of compulsive working was explained by other variables such as absorption, satisfaction with life, number of working hours over the weekend, motivation / focus on prevention and age. The results revealed a predictive model consisting of both individual and function / job / institution variables, which suggests that work addiction is a psychosocial phenomenon. The identified model can support new studies and interventions aimed at improving the quality of life at work, promoting health and well-being among managers.